2017
DOI: 10.1002/cne.24225
|View full text |Cite
|
Sign up to set email alerts
|

The ventromedial hypothalamic nucleus in the zebra finch (Taeniopygia guttata): Afferent and efferent projections in relation to the control of reproductive behavior

Abstract: Sex-specific mating behaviors occur in a variety of mammals, with the medial preoptic nucleus (POM) and the ventromedial hypothalamic nucleus (VMH) mediating control of male and female sexual behavior, respectively. In birds, likewise, POM is predominantly involved in the control of male reproductive behavior, but the degree to which VMH is involved in female reproductive behavior is unclear. Here, in male and female zebra finches, a combination of aromatase immunohistochemistry and conventional tract tracing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 128 publications
0
16
0
Order By: Relevance
“…However, other genes showing sparse expression in the hyperpallium, like SATB2 , are not enriched in the arcopallium and challenge this idea. Alternatively, a recent study reported a sparse population of nidopallium projection neurons with extratelencephalic targets (Wild, 2017), further highlighting the potential cell type similarities between the hyperpallium and nidopallium subdivisions. Further molecular profiling using single cell/nuclei RNA sequencing technology is necessary to test these hypotheses and aid in our understanding of the evolutionary relationships of these cell types across vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, other genes showing sparse expression in the hyperpallium, like SATB2 , are not enriched in the arcopallium and challenge this idea. Alternatively, a recent study reported a sparse population of nidopallium projection neurons with extratelencephalic targets (Wild, 2017), further highlighting the potential cell type similarities between the hyperpallium and nidopallium subdivisions. Further molecular profiling using single cell/nuclei RNA sequencing technology is necessary to test these hypotheses and aid in our understanding of the evolutionary relationships of these cell types across vertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…However, Box 3. Neurophysiological pathways for acoustic developmental programming Some non-auditory brain regions are responsive to sound Neurophysiological responses to sound can be observed in several brain regions that are not thought to be primarily auditory in their functions [109][110][111]. In particular, the hippocampus is known to respond to some particular acoustic features of music and songs in both humans [111] and birds [112], including during development [113].…”
Section: Evolutionary and Ecological Implications Of Prenatal Acoustic Developmental Plasticitymentioning
confidence: 99%
“…The arcopallium generates two prominent projections. The viscerolimbic zone is the origin of the hypothalamic part of the occipitomesencephalic tract (HOM), a prominent descending projection to subpallial structures, including the medial and lateral hypothalamus and the limbic areas of the striatum (Atoji et al, 2006;Davies, Csillag, Szekely, & Kabai, 1997;Wild, 2017;Zeier & Karten, 1971). Whereas the sensorimotor arcopallium, along with a minor contribution from the PoA, is the origin of the OM, which reaches several thalamic, mesencephalic, and brain stem areas (Zeier & Karten, 1971).…”
Section: Introductionmentioning
confidence: 99%